Matteo 7: Le opere di amore, la vera giustizia - Estrada, Bernardo (Liber Annuus, 2018)
Abstract The present study of Matt 7:1-29 should be considered not only as a substantial part of the discourse on the mountain but also as its conclusion. This is an important section of the first discourse of Jesus in Matthew which summarizes the essential message of the Gospel and outlines its main ethical-theological characteristics. Attention is drawn firstly to the initial part of Matt 7, which culminates with the golden rule (Matt 7:12), that constitutes the end of the inclusion introduced by the antitheses and connoted by the key words